A Monte Carlo ray‐tracing simulation of coherent X‐ray diffractive imaging. (27th November 2019) - Fevola, Giovanni; Bergbäck Knudsen, Erik; Ramos, Tiago; Carbone, Dina; Wenzel Andreasen, Jens
Abstract : Monte Carlo ray tracing is successfully used to simulate coherent diffractive imaging with a Huygens' wavelets‐based approach. Abstract : Coherent diffractive imaging (CDI) experiments are adequately simulated assuming the thin sample approximation and using a Fresnel or Fraunhofer wavefront propagator to obtain the diffraction pattern. Although this method is used in wave‐based or hybrid X‐ray simulators, here the applicability and effectiveness of an alternative approach that is based solely on ray tracing of Huygens wavelets are investigated. It is shown that diffraction fringes of a grating‐like source are accurately predicted and that diffraction patterns of a ptychography dataset from an experiment with realistic parameters can be sampled well enough to be retrieved by a standard phase‐retrieval algorithm. Potentials and limits of this approach are highlighted. It is suggested that it could be applied to study imperfect or non‐standard CDI configurations lacking a satisfactory theoretical formulation. The considerable computational effort required by this method is justified by the great flexibility provided for easy simulation of a large‐parameter space.